2006
DOI: 10.1063/1.2185587
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary stability of anisotropic femtosecond direct-written structures embedded in silica glass

Abstract: In this letter we report the different response to temperature displayed by isotropic femtosecond written structures ͑type I_fs͒, and anisotropic ones ͑type II_fs͒, which are characterized by the presence of a self-assembled subwavelength periodic structure within the irradiated volume. We observe that the anisotropic structures display an extraordinary annealing behavior, namely, their photoinduced change in refractive index increases with the annealing temperature. We explain our experimental results with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 15 publications
7
66
0
Order By: Relevance
“…Both ¼ and ½ waveplates and combinations therefore are readily fabricated, allowing total integration of birefringent components and waveguides with unprecedented precision and resolution. These silica waveplates exhibit enormous advantages including a broad spectral range from UV to IR and high thermal stability (no decay after 2 h @ 1000 °C [30] from which an estimated lifetime of about 300 million years at room temperature) can be obtained. This is primarily due to the intrinsic structures (nanoporous silica) and the absence of glued components found in commercial waveplates, and a much higher damage threshold (25 ± 3 J/cm², at λ = 1064 nm, 3.5 ns, 10 Hz [31]).…”
Section: Discussionmentioning
confidence: 99%
“…Both ¼ and ½ waveplates and combinations therefore are readily fabricated, allowing total integration of birefringent components and waveguides with unprecedented precision and resolution. These silica waveplates exhibit enormous advantages including a broad spectral range from UV to IR and high thermal stability (no decay after 2 h @ 1000 °C [30] from which an estimated lifetime of about 300 million years at room temperature) can be obtained. This is primarily due to the intrinsic structures (nanoporous silica) and the absence of glued components found in commercial waveplates, and a much higher damage threshold (25 ± 3 J/cm², at λ = 1064 nm, 3.5 ns, 10 Hz [31]).…”
Section: Discussionmentioning
confidence: 99%
“…20),21) It was also observed that the femtosecond laser written structures of type I-fs and type II-fs display the different response to increased temperature and in particular the structures of type II-fs demonstrate the extraordinary behavior, whose refractive index change increases with temperature. 15) An amplified, mode-locked Ti: Sapphire laser operating at a wavelength of 800 nm, with 200 fs pulse duration and 100 kHz repetition rate, was utilized to fabricate the structures to be tested. The laser beam was linearly polarized and focused with a 10 × objective.…”
Section: Extraordinary Stability Of Form Birefringence Produced By Fementioning
confidence: 99%
“…14) The extraordinary stability of these nanogratings has also been reported. 15) Embedded micro-reflectors, 9) retardation plates, 13) and micro-fluidic channels 16) based on these nanostructures have been reported; however their optimization requires a systematic characterization of the properties of the periodic structures ver- Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…However the main region of interest justifying the use of these lasers is the Type II regime since changes in this regime are significantly more stable, up to 1000 ℃ [29,30]. Type II gratings written by using energies above T2 damage threshold [31] of the glass lead to very stable gratings.…”
Section: Application Of Femtosecond Lasersmentioning
confidence: 99%